2016
DOI: 10.1007/s11274-016-2105-5
|View full text |Cite
|
Sign up to set email alerts
|

Lichen secondary metabolite evernic acid as potential quorum sensing inhibitor against Pseudomonas aeruginosa

Abstract: Cystic Fibrosis is a genetic disease and it affects the respiratory and digestive systems. Pseudomonas aeruginosa infections in Cystic Fibrosis are presented as the main cause for high mortality and morbidity rates. Pseudomonas aeruginosa populations can regulate their virulence gene expressions via the bacterial communication system: quorum sensing. Inhibition of quorum sensing by employing quorum sensing inhibitors can leave the bacteria vulnerable. Therefore, determining natural sources to obtain potential … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 38 publications
1
16
0
Order By: Relevance
“…E. prunastri and evernic acid have already been studied for their antiproliferative and antimicrobial activities [ 31 , 32 ]. In a recent publication, the effect of evernic acid on bacterial biofilm has been evaluated and this depside has demonstrated a capacity to inhibit Pseudomonas aeruginosa quorum sensing systems [ 33 ].…”
Section: Resultsmentioning
confidence: 99%
“…E. prunastri and evernic acid have already been studied for their antiproliferative and antimicrobial activities [ 31 , 32 ]. In a recent publication, the effect of evernic acid on bacterial biofilm has been evaluated and this depside has demonstrated a capacity to inhibit Pseudomonas aeruginosa quorum sensing systems [ 33 ].…”
Section: Resultsmentioning
confidence: 99%
“…gordonii and P. gingivalis are oral bacteria initiating the formation of dental plaques contributing in turn to the onset of dental caries and periodontal diseases as well as their progression [10]. We have previously demonstrated that these bacteria are sensitive to new drugs which are of natural origin as they are derived from lichen secondary metabolites [7,25]. However, its antibacterial mechanisms are still unknown.…”
Section: Resultsmentioning
confidence: 99%
“…Significance was accepted when the P value was < 0.05. There was no difference between the bactericidal activities on these two bacteria [18] 16sRNA CGGTCCAGACTCCTACGGGAGGCAGC A GCGTGGACTACCAGGGTATCTAATCC [19] mechanism of the bactericidal capabilities of AMPs mainly includes the destructive effects on bacterial cell walls and membranes. Besides their direct antimicrobial function on susceptible bacteria, AMPs have multiple roles as mediators in the inflammations and other diseases [21].…”
Section: Discussionmentioning
confidence: 99%